2011
DOI: 10.1123/pes.23.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Physical Self-Perceptions and Associations With Physical Activity During Adolescence

Abstract: The purpose of this study was to examine adolescents' physical self-perceptions and their associations with physical activity using a longitudinal perspective. Utilizing data from the Physical Activity in Scottish Schoolchildren (PASS) study, changes in exercise self-efficacy, perceived competence, global self-esteem and physical self-worth were assessed among a sample of 641 Scottish adolescents from age 11-15 years. Girls reported lower levels of perceived competence, self-esteem and physical self-worth than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
55
0
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 34 publications
8
55
0
13
Order By: Relevance
“…Although perceived physical competence repeatedly has been reported to be stronger among boys (Kenneth R Fox & Corbin, 1989;Inchley et al, 2011), research has, to our knowledge, not previously identified perceived physical competence to have a different impact on girls' intentions to be physically active compared to boys'. Findings from this moderation analysis are thus interesting.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although perceived physical competence repeatedly has been reported to be stronger among boys (Kenneth R Fox & Corbin, 1989;Inchley et al, 2011), research has, to our knowledge, not previously identified perceived physical competence to have a different impact on girls' intentions to be physically active compared to boys'. Findings from this moderation analysis are thus interesting.…”
Section: Discussionmentioning
confidence: 59%
“…Physical activity identity, on the other hand, appeared to be a strong mediator in both genders. Many studies identify girls as less physically active than boys (Anderssen & Andersen, 2004;Crocker, Eklund, & Kowalski, 2000;Kenneth R Fox & Corbin, 1989) and researches have argued for the promotion of physical literacy and confidence among girls to stimulate subsequent physical activity participation (Kenneth R Fox & Corbin, 1989;Inchley, Kirby, & Currie, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Por último, en este sentido, dado el tradicional comportamiento diferencial de hombres y mujeres en cuanto a las autopercepciones (Altintas y Asci, 2008;Esnaola, 2009;Welk y Eklund, 2005) y a la actividad físico-deportiva (Crocker et al, 2006;Haugen et al, 2011;Inchley et al, 2011), este estudio se planteaba también el objetivo de precisar diferencias asociadas al sexo en los resultados anteriores. Los resultados del estudio muestran que, mientras que en el caso de las mujeres,las cuatro dimensiones del autoconcepto físico manifiestan influencia sobre la actividad físico-deportiva, en el caso de los hombres ese influjo deriva tan sólo desde las dimensiones de condición física y de atractivo.…”
Section: Discussionunclassified
“…En una muestra de adolescentes noruegos (Raustorp et al, 2005), las autopercepciones físicas predicen el 20% de la actividad de los varones y tan sólo el 4% de la de las mujeres. En Escocia, sendos estudios (Inchley et al, 2011;Knowles et al, 2009) verifican que la autopercepción de su condición física de las mujeres y de la competencia atlética de los hombres predice también su actividad física. Por último, la percepción de la competencia atlética y de la fuerza, así como el autoconcepto físico general explican el 21% de la variabilidad de la actividad física de los varones; en tanto que la autopercepción de la competencia atlética y del atractivo, así como el autoconcepto físico general explican el 14% de la variabilidad de la actividad física de las mujeres en un estudio realizado en Estonia (Raudsepp, Liblik, y Hannus, 2002).…”
unclassified
See 1 more Smart Citation